Collaborative Barriers Among University - Industry - Policy (U-I-P) Entities on Environmental Matters: A Case Study in Sarawak, Malaysia - Manyie, Janice; James Gerusu, Geoffery; Roland Kueh Jui Heng, (Technium Social Sciences Journal, 2020)
Realizing the importance of practicing environmental concern, it is needed to understand the tools used to tackle the issues. In this study, university – industry – policy (U-I-P) entities collaboration is a significant approach that was viewed to be the success factor towards the efforts of tackling environmental issues. Collaboration work, which involves different entities benefit in a way that pushes the entities to move towards shared objectives and goals which is to improve the environmental condition. However, although the significance of U-I-P entities collaboration was known and the linkages among U-I-P entities has started, there are still limited information on the practice of collaboration specifically on the U-I-P entities linkage structures on environmental matters in Sarawak. Thus, there is a need to identify the barriers and success factor in order to develop successful collaboration. This study addressed the gap through a mixed method of qualitative and quantitative approaches which the data were collected from 199 respondents based on a face to face interview using structured questionnaires in the major divisions of Sarawak. Drawing from a large scale of study, the study explores the status of collaboration and the barriers of collaboration in Sarawak. Findings indicated that cost, private knowledge and knowledge barrier to be a major hurdle that inhibit the development of collaboration. The assessment suggested that more efforts to increase awareness on collaboration be disseminated.